Incidence of Road Traffic Injury and Associated Factors among Patients Visiting the Emergency Department of Tikur Anbessa Specialized Teaching Hospital, Addis Ababa, Ethiopia - Tiruneh, Bewket Tadesse; Dachew, Berihun Assefa; Bifftu, Berhanu Boru (Emergency Medicine International, 2014)
Background. Road traffic injuries are a major public health issue. The problem is increasing in Africa. Objective. To assess the incidence of road traffic injury and associated factors among patients visiting the emergency department of Tikur Anbessa Specialized Teaching Hospital, Addis Ababa, Ethiopia. Methods. Institutional based cross-sectional study design was conducted. A total of 356 systematically selected study subjects were included in the study. Bivariate and multivariate logistic regressions were performed to identify associated factors with road traffic injury. Odds ratios with 95% confidence interval were computed to determine the level of significance. Results. The incidence of road traffic injury in the emergency department of Tikur Anbessa Specialized Teaching Hospital was 36.8%. Being a farmer (AOR = 3.3; 95% CI = 1.06–10.13), conflict with family members (AOR = 7.7; 95% CI = 3.49–8.84), financial problem (AOR = 9.91; 95% CI = 4.79–6.48), psychological problem (AOR = 17.58; 95% CI = 7.70–12.14), and alcohol use (AOR = 2.98; 95% CI = 1.61–5.27) were independently associated with road traffic injury. Conclusion and Recommendation. In this study the incidence of road traffic injury was high. Alcohol is one of the most significant factors associated with Road Traffic Injury. Thus urgent education on the effect of alcohol is recommended.